Travelers, immigrants, inmates : essays in estrangement - Bartkowski, Frances, 1948- (University of Minnesota Press, 1995)
Uses travel writings, U.S. immigrant autobiographies, and concentration camp memoirs to illustrate how tales of dislocation present readers with a picture of the complex issues surrounding mistaken identities. Bartkowski's elegantly written and incisive book stands at the crossroads of contemporary thought in cultural studies and ethnicity, race and gender, nationalism, and the politics and poetics of identity.